2018
DOI: 10.1097/md.0000000000010901
|View full text |Cite
|
Sign up to set email alerts
|

High loss to follow-up of children on antiretroviral treatment in a primary care HIV clinic in Johannesburg, South Africa

Abstract: Outcomes of HIV-infected children have improved dramatically over the past decade, but are undermined by patient loss to follow-up (LTFU). We assessed patterns of LTFU among HIV-infected children receiving antiretroviral treatment (ART) at a large inner-city HIV clinic in Johannesburg, South Africa between 2005 and 2014.Demographic and clinical data were extracted from clinic records of children under 12 years. Differences between characteristics of children retained in care and LTFU were assessed using Wilcox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
19
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 39 publications
10
19
6
Order By: Relevance
“…The interview results revealed that waiting time for the consultations, lack of understanding of how to follow-up, compounded by stigma and fear of disclosure to partners, contributed to LTFU especially at the PCR results stage and the follow-up to ART initiation. These finding tend to corroborate results from other studies and trials in low resources contexts (10)(11)(12)(13)(14) . HIV testing and ART initiation coverage for mothers tends be quite high, but EID and pediatric HIV care and treatment coverage are hampered by lack of patient tracking mechanisms, long waiting times for test results, and inadequate counseling and support for mothers to help them understand and navigate each step in the care cascade.…”
Section: Discussionsupporting
confidence: 91%
“…The interview results revealed that waiting time for the consultations, lack of understanding of how to follow-up, compounded by stigma and fear of disclosure to partners, contributed to LTFU especially at the PCR results stage and the follow-up to ART initiation. These finding tend to corroborate results from other studies and trials in low resources contexts (10)(11)(12)(13)(14) . HIV testing and ART initiation coverage for mothers tends be quite high, but EID and pediatric HIV care and treatment coverage are hampered by lack of patient tracking mechanisms, long waiting times for test results, and inadequate counseling and support for mothers to help them understand and navigate each step in the care cascade.…”
Section: Discussionsupporting
confidence: 91%
“…The interview results revealed that waiting time for clinic visits, and lack of understanding of how to followup added to stigma and fear of disclosure to partners, and contributed to LTFU especially at the PCR results stage and the follow-up to ART initiation. These findings tend to corroborate results from other studies and trials in low resources contexts [10][11][12][13][14]. HIV testing and maternal ART initiation coverage tends be quite high, but EID and pediatric HIV care and treatment coverage are hampered by lack of patient tracking mechanisms, long waiting times for test results, and inadequate counseling and support for mothers to help them understand and navigate each step in the care cascade.…”
Section: Discussionsupporting
confidence: 84%
“…The EID care and treatment cascade has proven challenging in many developing countries, including Mozambique [1,[9][10][11][12][13][14]. Loss-to-follow-up (LTFU) can occur at multiple steps and effective EID is further impeded by human resource constraints, lack of parental understanding for how to navigate care, laboratory stock-outs, and difficulty with patient tracking [9][10][11][12][13][14]. One recent meta-analysis indicated that most attrition occurs in the first 6 months of follow-up and 39% of exposed infants were not in care after 18 months, therefore interventions early in the EID cascade might have greater impact on LTFU [14].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, more than half (52%) of the study participants were classified as WHO stage I and II; however, about 73.2% of the study participants included in a study from South Africa were classified as WHO stage III and IV [27]. Evidence suggests that HIV-infected children classified as severe disease stage (WHO stage III and IV) at ART initiation were more prone to LTFU as compared to those children classified as WHO stage I and II [11,31]. This study found that the incidence rate of LTFU within one year of ART initiation was 8.2 (95%, CI: 5.7, 11.7) per-100 child years of observation.…”
Section: Plos Onementioning
confidence: 99%